An Indian perspective on One Health prescriptions - Madhuri Ramesh; Sheetal Patil; Adithya Pradyumna (Ecology, Economy and Society – The INSEE Journal)
This commentary offers a critical engagement with the Environment–Health Nexus Policy Guide released by the United Nations Economic and Social Commission for Asia and the Pacific (ESCAP) and the International Institute for Sustainable Development (IISD) in 2022–23. We find that it strikes a hitherto-elusive balance between concerns centred on human and environmental health. It can be also credited with adopting an intersectoral approach—essential for addressing current and emerging infectious diseases, especially those of zoonotic origin. We contend that it does not adequately engage with the implementation challenges faced by countries with resource constraints or dense human populations, such as those in South Asia, and typified by India. We hope that a perspective from India will help the global policy discussions on One Health to diversify itself.